2011
DOI: 10.1128/jb.05519-11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Glucosamine/Glucosaminide N -Acetyltransferase of Clostridium acetobutylicum

Abstract: Many bacteria, in particular Gram-positive bacteria, contain high proportions of non-N-acetylated amino sugars, i.e., glucosamine (GlcN) and/or muramic acid, in the peptidoglycan of their cell wall, thereby acquiring resistance to lysozyme. However, muramidases with specificity for non-N-acetylated peptidoglycan have been characterized as part of autolytic systems such as of Clostridium acetobutylicum. We aim to elucidate the recovery pathway for non-N-acetylated peptidoglycan fragments and present here the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…As for AC7_0201, encoding sodium/solute symporter family proteins, a bacterial homolog of the apical sodium-dependent bile acid transporter was detected in Neisseria meningitides (51), implying that deoxycholate can be absorbed in the cytoplasm in NCTC8239 through this symporter. Gcn5-related N-acetyltransferase is required for the recovery of non-N-acetylated muropeptides during cell wall turnover in Clostridium acetobutylicum (52). dapA and dapB encode the precursor synthetic enzymes for dipicolinic acid and were activated during sporulation in Bacillus cereus (53,54).…”
Section: Dca-induced Sporulation In C Perfringens Strain Nctc8239mentioning
confidence: 99%
“…As for AC7_0201, encoding sodium/solute symporter family proteins, a bacterial homolog of the apical sodium-dependent bile acid transporter was detected in Neisseria meningitides (51), implying that deoxycholate can be absorbed in the cytoplasm in NCTC8239 through this symporter. Gcn5-related N-acetyltransferase is required for the recovery of non-N-acetylated muropeptides during cell wall turnover in Clostridium acetobutylicum (52). dapA and dapB encode the precursor synthetic enzymes for dipicolinic acid and were activated during sporulation in Bacillus cereus (53,54).…”
Section: Dca-induced Sporulation In C Perfringens Strain Nctc8239mentioning
confidence: 99%
“…Homology searching using MASCOT PMF indicated that the calcite-specific proteins are related to putative N-acetyltransferase YitH (GenBank accession no. CAB12939) (15,16,21), which is a member of the acetyltransferase family in B. subtilis. The enzyme N-acetyltransferase catalyzes the transfer of an acetyl group from acetyl coenzyme A (acetyl-CoA) to glucosamine 6-phosphate, the precursor of N-acetylglucosamine, a constituent of the peptidoglycan cell wall of Gram-positive bacteria (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…CAB12939) (15,16,21), which is a member of the acetyltransferase family in B. subtilis. The enzyme N-acetyltransferase catalyzes the transfer of an acetyl group from acetyl coenzyme A (acetyl-CoA) to glucosamine 6-phosphate, the precursor of N-acetylglucosamine, a constituent of the peptidoglycan cell wall of Gram-positive bacteria (21,22). The thick peptidoglycan shell of endospores is known as the spore cortex and aids in survival during dormancy (23).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an enzyme from Clostridium acetobutylicum , referred to as GlmA, has been characterized and has been proposed to play such a role in cell wall rescue. 12 Importantly, GlmA shows high specificity for both glucosamine and chitosan fragments ( β −1 → 4-linked glucosamine residues).…”
mentioning
confidence: 99%